Improving Student Nurses’ Clinical-Reasoning Skills: Implementation of a Contextualised, Guided Learning Experience - Indriani Yauri; Robyn Nash; Joanne Ramsbotham (Faculty of Nursing Universitas Padjadjaran, 2019)
Well-developed clinical reasoning skills are central to the process of clinical judgement. However, the results of recent studies suggest that curricula and teaching approaches that support student nurses’ development of clinical reasoning skills have not yet been fully achieved. Cognitive apprenticeship offers a new approach to facilitate the development of complex thinking skills, for example, reasoning skills in making clinical decisions. This study examined the effect of an educational intervention utilizing principles of cognitive apprenticeship on students’ ability to apply clinical reasoning skills within the context of a purpose-built clinical vignette.A quasi-experimental, non-equivalent control-group design was used to evaluate the effect of the educational intervention on students’ accuracy, inaccuracy and self-confidence in clinical reasoning. Eighty-five undergraduate nursing students participated in the study. A purpose-built clinical vignette was utilised to collect data from study participants. Mixed-Design ANOVA with a significant level of p< 0.05 was employed. Both quantitative and qualitative data were collected. A statistically significant increase in students’ accuracy in clinical reasoning was found after the six-weeks educational intervention. Examination of the quantitative data at time 2 discovered a statistically significant higher accuracy in clinical reasoning score (p<0.00) of the intervention group as compared to the control group. Results from inaccuracy and self-confidence in clinical reasoning did not reach significance. Results from the qualitative data are reported separately. It is argued that interplay of small group discussion of domain specific case-scenarios and the provision of guided learning experience may play a role in achieving partially successful results. This study makes an important contribution to nursing education by providing evidence to understand how best to facilitate nursing students’ development of clinical reasoning.